(untitled) (Educação em Revista, 2025)
In Chile, building inclusive schools implies defining the role and actions of support teams in the School Integration Program (PIE). However, this program has been reported to develop simultaneous approaches (integrative/inclusive), rooted in deficit-based models and professional encapsulation, which hinder the professional actions of teams in school support situations. Thus, we seek to understand how PIE professionals define and intervene in educational support situations in 7 Chilean educational institutions. A qualitative methodology with a narrative-rhetorical approach is developed, examining 52 critical incidents, from which 10 exemplary cases are selected. The results highlight: 1) Difficulties with teaching and learning strategies, 2) Behavioral/disciplinary incidents of students, 3) Difficulties in collaborative work and 4) Difficulties in relations with families. The predominance of restricted-individualizing actions that privilege an integrative approach is discussed, in addition to mapping how professionals close/open their intervention scenarios. It is concluded that the methodological proposal provides enriching tools to deepen the definition and intervention of educational situations, and its relevance for initial and continuous training for education professionals.